Study of Statistical Quality Control (SQC) Methods in Analyzing Quality Control of Paving Block Products at PT. X - Sumiati; Nur Rahmawati; Tranggono; Dwi Sukma Donoriyanto; Minto Waluyo (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
PT. X is a manufacturing company that produces building materials. PT. X is still often faced with several problems including the frequent occurrence of defective products, especially in paving block products as one of its main products. The defects that often occur include products that are easily crushed, cracked, asymmetrical, not dry and also broken in some parts. The defects that occur affect the quality of the resulting product. The purpose of this study was to determine the most dominant percentage of defects to allow further treatment. The method used in this research is Statistical Quality Control (SQC). The SQC method uses several tools including check sheets, stratification, histograms, paretto diagrams, scatter diagrams, control charts, and cause and effect diagrams. Based on the results of the SQC study, the most dominant defects were easily crushed paving with a percentage of 38.34%, cracked paving with a percentage of 28.86%, broken paving in some parts with a percentage of 13.83%, asymmetrical paving with a percentage of 10.92%, and non-dry paving with a percentage of 8.05%.